High-sensitivity gas leak detection sensor based on a compact microphone array. (April 2021) - Li, Jian; Li, Yulin; Huang, Xinjing; Ren, Jiahao; Feng, Hao; Zhang, Yu; Yang, Xiaoxia
Highlights: A compact MEMS mic array-based sensor for detecting tiny gas leak is proposed. Sensor gain is equal to array element number if leak source azimuth is close to 0°. The sensor can detect 0.67 mL/s leak from a 0.1 mm hole at the distance of 20 cm. The sensor can detect 0.1 mL/s leak via listening to burst sound of invisible bubble. Abstract: Early detection of tiny leaks in gas-pressurized vessels and pipelines can prevent disasters. Algorithm and sensor developments can enable acoustic methods to achieve high-sensitivity online leak detection by monitoring the sound generated by a leak and propagating in air. In this study, a compact MEMS microphone array-based sensor is proposed to detect very small gas leaks. Numerical calculation and experiment results show that the sensor gain (compared to a single microphone) is equal to the array element number when the azimuth of the leak source relative to the sensor is close to 0°. The proposed sensor can detect leaks as small as 0.67 mL/s emitted from a 0.1 mm hole at a distance of 20 cm. The bubble method can be used to enable the sensor to detect even smaller leaks, as low as 0.1 mL/s, at a distance of 10 cm using the burst sound of an invisible bubble.